Gas Turbine Application to CO2 Pipeline: A Techno-Economic and Environmental Risk Analysis - El-Suleiman, Abdussalam (Cranfield University, 2014)
Gas Turbines (GTs) are used extensively in pipelines to compress gas at suitable points. The primary objective of this study is to look at CO2 return pipelines and the close coupling of the compression system with advanced prime mover cycles. Adopting a techno-economic and environmental risk analysis (TERA) frame work, this study conducts the modelling and evaluation of CO2 compression power requirements for gas turbine driven equipment (pump and compressor). The author developed and validated subroutines to implement variable stators in an in-house GT simulation code known as Variflow in order to enhance the off-design performance simulation of the code. This modification was achieved by altering the existing compressor maps and main program algorithm of the code. Economic model based on the net present value (NPV) method, CO2 compressibility factor model based on the Peng-Robinson equation of state and pipeline hydraulic analysis model based on fundamental gas flow equation were also developed to facilitate the TERA of selected GT mechanical drives in two case scenarios. These case scenarios were specifically built around Turbomatch simulated GT design and off-design performance which ensure that the CO2 is introduced into the pipeline at the supercritical pressure as well as sustain the CO2 pressure above a minimum designated pressure during transmission along an adapted real life pipeline profile. The required compression duty for the maximum and minimum CO2 throughput as well as the operation site ambient condition, guided the selection of two GTs of 33.9 MW and 9.4 MW capacities. At the site ambient condition, the off design simulations of these GTs give an output of 25.9 MW and 7.6 MW respectively. Given the assumed economic parameters over a plant life of 25 years, the NPV for deploying the 33.9 MW GT is about £13.9M while that of the 9.4 MW GT is about £1.2M. The corresponding payback periods (PBPs) were 3 and 7 years respectively. Thus, a good return on investment is achieved within reasonable risk. The sensitivity analysis results show a NPV of about £19.1M - £24.3M and about £3.1M - £4.9M for the 33.9 MW and 9.4 MW GTs respectively over a 25 - 50% fuel cost reduction. Their PBPs were 3 - 2 years and 5 - 4 years respectively. In addition, as the CO2 throughput drops, the risk becomes higher with less return on investment. In fact, when the CO2 throughput drops to a certain level, the investment becomes highly unattractive and unable to payback itself within the assumed 25 years plant life. The hydraulic analysis results for three different pipe sizes of 24, 14 and 12¾ inch diameters show an increase in pressure drop with increase in CO2 throughput and a decrease in pressure drop with increase in pipe size for a given throughput. Owing to the effect of elevation difference, the 511 km long pipeline profile gives rise to an equivalent length of 511.52 km. Similarly, given the pipeline inlet pressure of 15 MPa and other assumed pipeline data, the 3.70 MTPY (0.27 mmscfd) maximum average CO2 throughput considered in the 12¾ inch diameter pipeline results in a delivery pressure of about 15.06 MPa. Under this condition, points of pressure spikes above the pipeline maximum operating allowable pressure (15.3 MPa) were obtained along the profile. Lowering the pipeline operating pressure to 10.5 MPa gives a delivery pressure of about 10.45 MPa within safe pressure limits. At this 10.5 MPa, over a flat pipeline profile of same length, the delivery pressure is about 10.4 MPa. Thus, given the operating conditions for the dense phase CO2 pipeline transmission and the limit of this study, it is very unlikely that a booster station will be required. So also, compressing the CO2 to 15 MPa may no longer be necessary; which eliminates the need of combining a compressor and pump for the initial pressure boost in order to save power. This is because, irrespective of the saving in energy, the increase in capital cost associated with obtaining a pump and suitable driver far outweighs the extra expense incurred in acquiring a rated GT mechanical drive to meet the compression duty.
Keywords: Gas Turbine; CO2; Pipeline; Throughput; Power Generation; TERA; NPV